Road Safety Education during the Franco Regime: the first Children’s Traffic Parks in Majorca (1962-1975) - Barceló Bauzà, Gabriel; Gelabert Gual, Llorenç (Historia y Memoria de la Educación, 2019)
The situation brought about by economic growth that was visible in Spain between the end of the fifties and the beginning of the sixties of the last century exerted, to a greater or lesser extent, an influence on education. Proof of this was the introduction into the school of new curricular contents such as road education, which began to occupy its own space in school hours. This article presents an introduction to the children’s traffic parks that were created to instil road safety habits through real practice and which supplemented the theoretical training given in classrooms. Typical activities would include children engaged in role-playing, being drivers, pedestrians or traffic wardens. This article focuses on the parks in Majorca —an island te rritory that saw a major increase in road traffic in the last thirty years of the 20th century, mainly due to population growth resulting from the tourism boom and to a highgrowth economic outlook. In order to put together an inventory of the existing parks and to undertake an analysis of their legacy and contributions, we have used a series of sources (written, oral and illustrated) that has enabled us to provide empirical data on the context in which they were created, on those responsible for promoting them, and on the importance of their introduction under the auspices of a new education programme.